Relationship between anxiety, depression and CD4+ T lymphocytes in patients with Human Immunodeficiency Virus (HIV) in a general hospital in Lima - Grados-Castro, Diana (2023)
Objective: To determine the relationship between anxiety, depression and CD4+ T lymphocyte count in a sample of people carrying the human immunodeficiency virus (HIV). Methodology: Observational and analytical study. A total of 144 HIV-positive patients were evaluated. The Hospital Anxiety and Depression Scale (HADS) was used. Results: The sample’s mean age was 41 years. Most of the probands were male (71.5%), single (86.1%) and with secondary education (57.6%). The average length of the disease was 7.7 years, 11.1% presented some comorbidity, and 95.1% used tenofovir as treatment. Thirty-four and 16.7% presented some level of anxiety and depression, respectively. Patients at the AIDS stage presented higher levels of anxiety (p < 0.001) and depression (p < 0.001). Patients with HIV and medical comorbidities had higher levels of depression (p = 0.044). Anxiety (ρ = -0.516, p = 0.01) and depression (ρ = -0.509; p = 0.01) levels were related to CD4+ T lymphocyte count. Conclusion: Higher levels of depression were found in patients with comorbidities and AIDS stage, and higher levels of anxiety were found in patients at the AIDS stage. In addition, a significant indirect relationship was found between anxiety and depression levels and the CD4+ T cell count. Training healthcare professionals to screen for anxiety and depressionin order to improve the mental health of HIV patients, is highly recommended.